The Great Decoupling
XXXI, 264 p.
Keywords: The rise of China, a country thought to be very different from the dominant West led by the USA in terms of political systems and civilizational traditions, has profoundly unsettled the latter. Discussions about decoupling the West from China have been ongoing for several years now, and certain actions have already taken place to indicate that this is happening. What is the current state of affairs? What are the likely prospects? This book, one of the first attempts to address these issues as comprehensively as possible, aims to explore these questions. It is not only cross- and inter-disciplinary but also includes scholars from the Global South, the East, and the West. Mobo Gao, Professor of Chinese Studies at Adelaide University, has extensive experience at various universities in China, UK, US and Australia. He is known as a prolific author with several books and numerous articles and book chapters and for his insight into Chinese politics, Chinese language, culture and society, as well as Chinese migration to Australia and the mass media. Justin O’Connor is Professor of Cultural Economy at Adelaide University and a Visiting Professor at the School of Cultural Management, Shanghai Jiaotong University. Between 2012-18, he was a member of the UNESCO ‘Expert Facility’. He recently co-authored Red Creative: Culture and Modernity in China (Intellect), and Culture is Not an Industry (Manchester University Press). Baohui Xie, a Scholarly Teaching Fellow at Adelaide University, has extensive experience in global finance. His diverse research interests encompass Chinese politics, economics, media, religion, and language. Dr Xie is also an advanced-level interpreter accredited in China and a NAATI-certified translator for English and Chinese in both directions. Jack Butcher, a PhD Candidate and Adjunct Lecturer at Adelaide University, researches the security of East Asia and the Asia/Indo-Pacific. Jack recently published in the Australian Journal of International Affairs, the Lowy Interpreter, and co-edited Different Histories, Shared Futures: Dialogues on Australia-China (Palgrave Macmillan).